Evaluating the effects of mental health e-learning on the knowledge, attitudes and practices of allied and healthcare professionals in Senegal - Pierre-Emile Bruand; Thibaut Gelle; El Hadji Makhtar Ba; Jean Augustin Diegane Tine; Amy Fall Ndao; Line Kleinebreil; Driss Moussaoui; Pierre-Marie Preux; Farid Boumediene (Elsevier, 2024)
Background: Despite the widespread prevalence and substantial burden of mental disorders, they remain significantly underdiagnosed and undertreated. In low- and middle-income countries like Senegal, integrating mental health services into primary care represents the most feasible strategy to bridge the treatment gap. This study aimed to assess the effects of a mental health e-learning program on the knowledge, attitudes, and practices of allied and healthcare professionals in Senegal. Methods: An e-learning platform including 12 interactive modules was used to train 322 allied and healthcare professionals. We evaluated changes in knowledge, attitudes, and practices, as well as in satisfaction with knowledge and in self-assessed ability to diagnose and manage patients, by comparing data collected before and after the e-learning modules. Qualitative feedback on the satisfaction with the various components of the program was also collected via a post-training survey. Outcomes: Knowledge, attitudes and practices scores increased significantly for all modules. Additionally, scores related to satisfaction with knowledge and ability to diagnose and manage patients showed significant improvements (+77.0 % and +75.0 %, respectively), surpassing the gains observed in knowledge, attitudes, and practices scores (+19.2 %, +11.1 % and +15.0 %, respectively). Mean scores regarding participants' satisfaction with the various elements of the program ranged from 8.1 to 9.1, out of a maximum of 10. Conclusion: Although only a limited number of participants completed all 12 modules, the mental health e-learning program showed positive results on the knowledge, attitudes, and practices of participants. It also increased their confidence and was perceived as a very positive experience by learners.